Tinjauan Historis Akar Pencarian Ilmu dalam Islam - Asna Andriani (Tarbiyah Departement collaboration with AMCA, 2014)
According to Jacques C. Reiser opinion that during 500 years Islam was empowered whole world accompaniying by strength, science and a great civilization. There are many islamic contribution to the world’s civilization and education, such as finding some mathematic concepts, medicinal treatments, and gave contribution for renaisance and enlighment age in Europe. This progress which was produced by islamic civilization, especially the science field was previoused by moeslem spirit and effort within searching for the science before. This papper will explain the historical study abaut the foundation of islamic science searching and its developing started at prophet periode untill the middle age (Abbasiya periode).